If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 0 + -6 = 0 Reorder the terms: 0 + -6 + 2x = 0 Combine like terms: 0 + -6 = -6 -6 + 2x = 0 Solving -6 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = 0 + 6 2x = 0 + 6 Combine like terms: 0 + 6 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 0+y-6=0 | | 5(-8x-2y)=120 | | 3+2y-12=0 | | X+4-4=9-4 | | x^2-2(1/4)=0 | | u+x+y+z+80+90=100 | | 2/2/2/2/2 | | 9x-3+8x=3x+5-5x | | 0=x^3-3x^2+2x-24 | | 2x-1+2=x | | xy+5y=21 | | 4x^2+-37x+84=0 | | 3x-5y=43 | | (x-2)=3 | | 450/900 | | 20x+5=40 | | 5x^2=6x+1 | | 6x-7-5x= | | h/-8=-5 | | -8p+3=292 | | 8x+6=3x-2 | | x-6/5=4 | | -0.28=log(x) | | 5(4-x)=0 | | x^2+2x-9.24=0 | | x^2+2x-9.25=0 | | 27(x+5)=0 | | 11s=22 | | 44-y=200 | | x=4^(1/2) | | 3r-7=4r+9 | | 3r-7=4r+8 |